2020
DOI: 10.1080/21655979.2020.1754038
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Propofol inhibits migration and induces apoptosis of pancreatic cancer PANC-1 cells through miR-34a-mediated E-cadherin and LOC285194 signals

Abstract: Propofol has exhibited potent antitumor activity in pancreatic cancer cells in vitro and in vivo. The study aimed to investigate the anti-tumor mechanisms of propofol on pancreatic cancer PANC-1 cells in vitro. PANC-1 cells were exposure to concentration 20 μg/ml of propofol for 72 h. Long non-coding RNA LOC285194 siRNA LOC285194 siRNA, E-cadherin siRNA and microRNA-34a (miR-34a) inhibitor were used to investigate the effect of propofol on PANC-1 cells. miR-34a and LOC285194 were analyzed by quantitative real-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 60 publications
(72 reference statements)
0
19
0
Order By: Relevance
“…Cyclin D1 is a nuclear factor of cell cycle, which can induce cell proliferation [ 29 ]; Bcl-2, as a member of the Bcl family, inhibited the cell apoptosis. While the trend of Bax is opposite to that of Bcl-2, which is a kind of a pro apoptotic factor [ 30 ]. In this study, we confirmed that knockdown of REV7 further down-regulated the expressions of Cyclin D1 and Bcl-2, and up-regulated the Bax expression.…”
Section: Discussionmentioning
confidence: 99%
“…Cyclin D1 is a nuclear factor of cell cycle, which can induce cell proliferation [ 29 ]; Bcl-2, as a member of the Bcl family, inhibited the cell apoptosis. While the trend of Bax is opposite to that of Bcl-2, which is a kind of a pro apoptotic factor [ 30 ]. In this study, we confirmed that knockdown of REV7 further down-regulated the expressions of Cyclin D1 and Bcl-2, and up-regulated the Bax expression.…”
Section: Discussionmentioning
confidence: 99%
“…With the advancement of anesthesia techniques, recent studies mainly focus on potential biological roles of anesthetics in tumor development. For instance, propofol showed its antitumor activity in pancreatic cancer cells by affecting miR-34a-mediated LOC285194 and E-cadherin signals [19]. Fentanyl is a commonly used as an anesthesia that exerts its antitumor effects in many human cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Identifying the mechanisms that regulate VSMC apoptosis potentially may lead to novel therapeutic approaches that are more efficacious for these patients. Previous works showed that LOC285194 overexpression induced cell apoptosis in gastric carcinoma [ 28 ], pancreatic cancer [ 29 ] and colon cancer [ 10 ]. In the present study, we demonstrated that LOC285194 overexpression significantly induced A7r5 cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%